Biografi Kiyai Hj.Abd. Rahman Ambo Dalle dan sumbangannya dalam dakwah di Sulawesi Selatan, Indonesia - Muhammad Yusuf Khalid (Unit Penerbitan, KUIM, 2005)
Biography of Abd. Rahman Ambo Dalle, 1900-1996, a prominent Muslim scholar from Sengkang, South Sulawesi Province